The Role of Hydrogen Bond Interactions in Crystal Formation of Pyrrolo-Azines Alcohols - Marcel Mirel Popa; Mihai Răducă; Isabela C. Man; Florea Dumitrascu (Crystals)
New secondary alcohols of type Ar-CHOH-hetaryl and MeCHOH-hetaryl, the radical hetaryl being a pyrroloazine, were investigated in solid state by X-ray single-crystal diffraction analysis, Hirshfeld analysis and DFT methods to assess their crystallographic features. One of the most important features is the presence of the hydroxyl group bonded to an asymmetric carbon atom which was involved in strong hydrogen bonds. The driving force of crystal packing is H-bond with the O-H···O=C/N≡C bonds being considered as strong comparative to carboxylic acids. These structural properties and binding affinity might lead to enhanced bioavailability of these particular pyrrolo-azines